IT alignment in Malaysian public sector: E-Syariah as a case of study - Muhammad, Muhd. Rosydi (2009)
IT alignment has been receiving a considerable attention amongst IS scholars and researchers. Despite the growth of IT alignment literature, further review indicates that most of the studies are carried out in either commercial or private organizations. Drawing on the previous literature on the differences between public and private sectors, the effects of four antecedents of IT alignment namely; shared domain knowledge, stakeholder relationships, centralization and formalization are examined. It is further argued that high level of IT alignment in government sectors contributes towards the improvement of government’s performance. Using case study on the implementation of E-Syariah in Malaysia, researcher finds out that all antecedents except centralization and formalization have direct impacts towards IT alignment practice in public sector, which consequently improve the delivery of government services to the public.